TOPONIMI NAMA-NAMA DESA DI KECAMATAN BANTARKAWUNG KABUPATEN BREBES (KAJIAN ANTROPOLINGUISTIK) - Nuraeni, Wini; Mulasih, Mulasih (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
This research aims to describe the toponymic aspects of village names in Bantarkawung District, Brebes Regency. The approach used is an anthropolinguistic study, namely the toponymic aspect of village names. The method used in this research is descriptive analysis. The techniques of data collection used were observation and interview techniques. This research instrument uses triangulation techniques. The results of the research found that in Bantarkawung District, Brebes Regency there are three toponymic aspects of village names, namely: 1) the embodiment aspect which is divided into three parts including water background, topographic background and natural environmental background, there are eight villages, namely: Bantarkawung Village, Bantarwaru Village , Cibentang Village, Ciomas Village, Cinanas Village, Legok Village, Tambakserang Village, and Telaga Village; 2) the social aspect, namely the naming of villages taken from the names of previous figures who had positions in society, there are three villages, namely: Jipang Village, Terlaya Village, and Waru Village; 3) cultural aspects related to folklore and community belief systems in seven villages, namely: Bangshadow Village, Banjarsari Village, Karangpari Village, Kebandungan Village, Pangebatan Village, Pengarasan Village, Sindangwangi Village. Keywords: toponymy, village names, anthropolinguistics